PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA DAN KINERJA KARYAWAN PADA PT. MITRA UNGGUL PUSAKA SEGATI KECAMATAN LANGGAM - Hikmawati Sri; Marzolina Marzolina; Pramadewi Arwince (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of leadership and workenvironment on work discipline and employee performance at PT. Mitra UnggulPusaka Segati, Langgam District, totaling 104 people. Primary data wascollected using a questionnaire as an instrument to prove the results of the study,to test the hypothesis in this study using path analysis (path analysis with the helpof the SPSS program. The sampling technique that has been selected is the sensesmethod (104 employees at PT. Mitra Unggul Pusaka Segati). Langgam District).The results showed that: Leadership has a positive and significant effect onemployee work discipline. The work environment has a positive and significanteffect on employee work discipline. Leadership has a positive and significanteffect on employee performance through employee performance discipline. Thework environment has a positive and significant effect on employee performancethrough employee work discipline. Work discipline has a positive and significanteffect on the performance of employees of PT. Mitra Unggul Pusaka Segati Subdistrict Langgam. Keywords: Leadership, Work Environment, Work Discipline, EmployeePerformance.